Assessing for autism in adult psychiatry - Samuel Tromans; Pushpal Desarkar (BJPsych Open, 2023)
This editorial discusses a study by Nyrenius and colleagues in which they investigated rates of co-occurring psychiatric conditions and functioning in a population of adults referred to a Swedish psychiatric out-patient clinic, comparing those meeting DSM-5 diagnostic criteria for autism with their non-autistic peers.